Upaya Guru dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Tingkat Madrasah Ibtidaiyah dengan Menggunakan Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) - Agustian, Angga Badra; Endang, Ujang; Selamet, Selamet (Bestari, 2019)
This research is motivated by the low student learning outcomes in social studies learning in the third class of MIS Handapherang Buy and Sell. In addition, students' lack of interest in social studies learning is due to teacher-centered learning not to students. So that social studies are considered saturated and boring lessons. In an effort to improve student learning outcomes, researchers used the Learning Strategy to Increase Thinking Ability (SPPKB). The method used is the class action research method (PTK) model of Kurt Lewin. Data collection techniques used are observation, test or assessment techniques and description analysis techniques. After conducting research, the results of the study can be obtained as follows: 1) The ability of teachers to design social studies learning plans in the first cycle is 84; cycle II is 87; cycle III is 92.1. 2) The skills of teachers in teaching in the first cycle amounted to 84.6; cycle II is 89.4; the third cycle is 93.3. 3) Student learning outcomes in the first cycle of 72.5; cycle II is 86.6; cycle III is 95. This proves that SPPKB can improve student learning outcomes on social studies subjects in the class III MIS Buy and Sell Handapherang. The results of the analysis indicate that the proposed hypothesis is acceptable